2020
DOI: 10.7717/peerj.10493
|View full text |Cite
|
Sign up to set email alerts
|

Association between parenting and non-suicidal self-injury among adolescents in Yunnan, China: a cross-sectional survey

Abstract: Background Non-suicidal self-injury (NSSI) among adolescents is prevalent and its rate has increased in recent years worldwide. Previous studies had investigated the association between parenting and childhood NSSI, but little is known about the relationship between parental rearing and repetition and severity of NSSI. The aim of this study was to investigate associations of parenting with NSSI and its repetition and severity in a representative adolescent sample from southwestern China. Methods In this cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
13
1
Order By: Relevance
“…Based on the results of the analysis, we found that less emotional warmth from the father, maternal over-protection, and rejection were significantly associated with SH. This conclusion was in line with two previous studies, which suggested that adverse parenting styles were risk factors of SH and suicidal behaviors among a representative sample of 3653 Chinese adolescents [ 12 , 26 ]. Parental over-protection and rejection can take the form of a stricter attitude and a higher level of control, and they have a negative effect on a child’s confidence and independence, which may in turn lead to mental health issues [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the results of the analysis, we found that less emotional warmth from the father, maternal over-protection, and rejection were significantly associated with SH. This conclusion was in line with two previous studies, which suggested that adverse parenting styles were risk factors of SH and suicidal behaviors among a representative sample of 3653 Chinese adolescents [ 12 , 26 ]. Parental over-protection and rejection can take the form of a stricter attitude and a higher level of control, and they have a negative effect on a child’s confidence and independence, which may in turn lead to mental health issues [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, paternal and maternal parenting styles may exert different influences on the mental health and well-being of children, as suggested by recent findings [ 10 ]. Some studies revealed that negative parenting styles were also significantly related to SH in young people [ 11 , 12 ]. In this regard, understanding the developmental path of the association between parenting styles and SH is critical in order to devise intervention measures for SH related to parenting styles.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the prevalence rates of NSSI behaviors in adolescents within a year vary enormously from 6-44.3% [20][21]. The prevalence rate in this study is 4.2%, lower than the rates in previous studies, which may be attributed to the discrepancies in the age of the targeted subjects, questionnaires, de nitions of indices, social factors [22], as well as early implementation of mental health screening in primary and secondary schools in the west of China.…”
Section: Discussioncontrasting
confidence: 68%
“…Individuals with alexithymia appear to have difficulty coping with social and psychological stressors and are more inclined to use “addictive” patterns as a coping strategy to manage underlying feelings of distress [ 11 ]. Alexithymia has been recognized as an significant risk factor for a variety of psychological and behavioral problems, including maladaptive schemas [ 12 ], eating disorders [ 13 ], academic achievement [ 14 ], non-suicidal self-injury [ 15 ], etc. Furthermore, alexithymia has been widely associated with increased marijuana use [ 16 ], increased caffeine consumption [ 17 ], mobile phone addiction [ 11 ], and pathological gambling [ 18 ].…”
Section: Introductionmentioning
confidence: 99%